SKRINING FITOKIMIA DAN UJI SITOTOKSIK EKSTRAK ETANOL DAUN ANDONG MERAH (Cordyline fruticosa) - Usman, Yuri Pratiwi Utami; Ainun Jariah (JURNAL KATALISATOR, 2023)
Cordyline fruticosa is a plant used in traditional medicine. C. fruticosa plant is empirically efficacious for stopping bleeding, eliminating swelling, C. fruticosa leaves are efficacious as a wound medicine and medicine for hemorrhoids and flatulence. This study aims to screening for phytochemical compounds and to determine the potential for toxicity using the BSLT (Brine Shrimp Lethality Test) method and in C. fruticosa leaf extract. The research method starts with the samples extracted using the maceration method for 3 x 24 hours and is continued with remaceration using 70% ethanol solvent. Furthermore, phytochemical screening tests and cytotoxic tests were carried out using the BSLT (Brine Shrimp Lethality Test) method, which is one method that is widely used to search for new anticancer compounds derived from plants, testing using Artemia salina Leach shrimp larvae aged 48 hours with a concentration of 20, 40, 60, 80 and 100 µg/mL and seawater as a control. Observations Artemia salina Leach was observed for 24 hours. The results showed that the ethanol extract of red andong leaves contains a class of flavonoids, triterpenoids, saponins, and tannins. The LC50 value of the ethanol extract of red andong leaves, namely 60.36 µg/mL, is included in the toxic category